Lipase-catalyzed synthesis and characterization of copolymers from ethyl acrylate as the only monomer starting material - Rustoy, Eduardo Miguel; Sato, Yasuto; Nonami, Hiroshi; Erra Balsells, Rosa; Baldessari, Alicia (Polymer)
Several acrylic copolymers containing, at random, sequences of poly(ethyl acrylate) and poly(N-(2-hydroxyethyl)acrylamide) were obtained from ethyl acrylate as the only monomer starting material in a chain polymerization process, catalyzed by Candida antarctica lipase B. In the presence of ethanolamine, the enzyme not only catalyzes the chain polymerization of ethyl acrylate but also aminolysis the pendant ester groups. The products, characterized by FTIR, 1H and 13C NMR and UV-MALDI-TOF-MS, show low molecular weight and high monodispersity. The activity showed by C. antarctica lipase B in the polymerization reaction is a new example of enzyme promiscuity. Fil: Rustoy, Eduardo Miguel. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Unidad de Microanálisis y Métodos Físicos en Química Orgánica. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Unidad de Microanálisis y Métodos Físicos en Química Orgánica; Argentina Fil: Sato, Yasuto. Ehime University; Japón Fil: Nonami, Hiroshi. Ehime University; Japón Fil: Erra Balsells, Rosa. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Centro de Investigaciones en Hidratos de Carbono. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Centro de Investigaciones en Hidratos de Carbono; Argentina Fil: Baldessari, Alicia. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Unidad de Microanálisis y Métodos Físicos en Química Orgánica. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Unidad de Microanálisis y Métodos Físicos en Química Orgánica; Argentina